2004
DOI: 10.1158/1078-0432.ccr-03-0365
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as an Adjunct to CA125 in Detecting Recurrent Ovarian Cancer

Abstract: Purpose: CA125 is currently the only tumor marker to have a validated role in the postoperative monitoring of ovarian cancer. Osteopontin (OPN) is a putative plasma biomarker that was recently identified using high-throughput cDNA microarray technology. The purpose of this study was to test the hypothesis that OPN is a clinically useful adjunct to CA125 in detecting recurrent ovarian cancer.Experimental Design: Thirty-eight ovarian cancer patients had a single pretreatment blood sample and 200 postoperative sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 26 publications
(19 reference statements)
1
65
1
Order By: Relevance
“…9 Other biomarkers, including human kallikrein, HE4 and osteopontin, are under investigation and large screening trials are underway in the United Kingdom. [10][11][12][13] Efforts to use multiple biomarkers, although encouraging, have met with mixed results. One study comparing the serologic detection of multiple biomarkers demonstrated comparable sensitivity (79% and 82%) and an improvement in specificity from 68% to 88%.…”
Section: Early Detection Of Ovarian Cancermentioning
confidence: 99%
“…9 Other biomarkers, including human kallikrein, HE4 and osteopontin, are under investigation and large screening trials are underway in the United Kingdom. [10][11][12][13] Efforts to use multiple biomarkers, although encouraging, have met with mixed results. One study comparing the serologic detection of multiple biomarkers demonstrated comparable sensitivity (79% and 82%) and an improvement in specificity from 68% to 88%.…”
Section: Early Detection Of Ovarian Cancermentioning
confidence: 99%
“…Osteopontin has long been implicated in the process of carcinogenesis, progression, and metastatic dissemination of several human tumors including lung cancer [14][15][16][17][18][19][20][21][22] . This study evaluated the association of circulating osteopontin levels with tumor progression using clinical samples from the patients who underwent surgical resection and mediastinal lymphadenectomy for their NSCLC and have taken no any anti-cancer therapy till time of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…In an additional study, an elevated serum CA125 (≥35 units/mL) and preoperative ultrasound findings of solid or complex tumors yielded a PPV of 84.7%, a NPV of 92.4% and correctly identified 77.3% of patients with early stage disease 70 . Additional potential serum biomarkers have been identified [72][73][74] and extensively examined for the detection of ovarian cancer [75][76][77] . Human epididymis protein 4 (HE4) is a biomarker overexpressed by both serous and endometrioid ovarian cancers 78 and is expressed by 32% of ovarian cancers lacking CA125 expression 76 .…”
Section: What Role Do Biomarkers Play In the Screening Of Ovarian Canmentioning
confidence: 99%